CEMENT PRODUCTION FORECAST IN INDONESIA FOR THE PERIOD OF 2026-2030 USING VARIOUS FORECASTING METHODS AND BUSINESS INTELLIGENCE WITH POWERBI - Arfadillah Damaera Agus; Lina Gozali; I Wayan Sukania (Jurnal Ilmiah Teknik Industri, 2025)
Indonesia’s cement manufacturing industry is currently in oversupply. According to Businesswire – A subsidiary of Berkshire Hathaway – Indonesia’s cement industry is currently navigating a structural imbalance marked by oversupply, this makes production planning very important to mitigate overproduction in the future. This journal collaborates various forecasting methods and machine learning with production planning. Machine learning is one of the technological breakthroughs of the 20th century. If used correctly, machine learning can be very beneficial for production planning combined with various forecasting methods. Historical data are used as reference to forecast into the future. Based on the test results, Decomposition method is the best forecasting method in this case. The output of the forecast is a business intelligence dashboard that supports decision makers in strategic planning.